Psychological Aspects Of Leader Traits In Boys And Girls In Different Family Settings - Murotmusaev Komiljon Buribaevich; Boykulova Mokhinur; Abduakhadova Mehribonu (Genius Journals, 2022)
The problematic of this article was the identification during the study of leadership qualities in boys and girls of school age, and the possibility of their implementation. The authors considered the issue of leadership differences between boys and girls. The issues of family conditions for the qualitative approach to the development of leadership qualities in children were determined and analyzed.
Keywords: Leadership; family; boy leader; education